FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN INDIKATOR MUTU KEPERAWATAN DI RUANG RAWAT INAP RSUD DR. DRADJAT PRAWIRANEGARA - Dian Rosdiana; Muhammad Hadi; Suhendar Sulaeman (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Nursing service quality is a process of activities carried out by the nursing profession in meeting the needs of patients in maintaining the condition in terms of the biological, psychological, social, and spiritual aspects of the patient. The purpose of this study was to determine factors related to the quality of nursing services in the inpatient room of RSUD dr. Dradjat Prawiranegara Serang Regency, Banten Province, 2020. This study used cross sectional. The sample of the study were 353 respondent which used two proporsion different test. The instrument of this study used valid and realible questionnaire. For testing Bivariat used Chi-square test while multivariat testing used double logistic regration. the result of this study of caring research, nurse competence, inpatient care facilities, knowledge, and costs p-value 0.049 <0.05 which indicated that there was any significant correlation toward quality of nursing services. Meanwhile, the dominant factor toward quality of nursing services was caring with Odds Ratio 3.947. Caring, nurse competence, inpatient facilities, knowledge and costs related to the quality of nursing services, is expected to dr. Dradjat Prawiranegara can maintain and develop for the better.